A STUDY ON THE ‘THINGS’ IN CHINUA ACHEBE’S THINGS FALL APART - Sahoo, Sudarsan (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The study examines the reason of the fall of the Umuofia tribe and the main character ,Okonkwo.There are certain events , both internally and externally , caused things to fall apart.This study divides ‘things’ into two main subtitles: Okonkwo dreams that fall apart and the tribal System that falls apart.These subtitles include main influences of the changes that occur in the book. The first chapter includes the events such as Ikemefuna’s death, Nwoye’s conversion, Okonkwo’s desire to rule the tribe etc.The second chapter includes the reasons for Okonkwo’s exile, the arrival of christianity, the death of python,tribe’s not acting as one.